Continuous Renal Replacement Therapy and Extracorporeal Membrane Oxygenation in Cardias Surgery - S. V. Kolesnikov; A. S. Borisov; I. A. Kornilov; V. V. Lomivorotov (Общая реаниматология)
Objective: to analyze the combined use of extracorporeal membrane oxygenation (ECMO) and continuous renal replacement therapy with switching into the ECMO circuit in cardiac surgical patients over 18 years of age and to reveal predictors of a fatal outcome in this combination of auxiliary organ support techniques. Materials and methods. The retrospective cohort study postoperatively used a combination of ECMO and continuous renal replacement therapy in 27 cardiac surgical patients aged over 18 years with severe cardiopulmonary insufficiency concurrent with acute kidney lesion. In all cases, the continuous renal replacement therapy circuit was switched into the line after an ECMO pump. The end points of the study were the duration of dialysis-dependent acute renal failure, the frequency of complications, and hospital mortality. Results. In all cases with a favorable outcome, the duration of continuous renal replacement therapy was 3 days longer than that of ECMO. There were no cases of recovery if the duration of continuous renal replacement therapy was shorter than that of ECMO and the duration of the latter was more than 10 days. The duration of sympathomimetic support (>3.5 days ) was shown to be an independent and significant predictor of death (AUC 0.99; CI 99.9%, 0.96—1.0) in the patients receiving continuous renal replacement therapy and ECMO. It was established that the number of inotrophic drugs (>2) and the highest lactate level (>1.99 mmol/l) could be used to predict hospital mortality in patients with acute kidney injury and severe cardiopulmonary insufficiency (AUC 0.85 and 0.86; sensitivity/specificity 0.83/0.67 and 0.86/0.67, respectively).Conclusion. The concurrent use of ECMO and continuous renal replacement therapy in severe cardiac surgical patients with potentially reversible cardiopulmonary insufficiency and acute kidney injury is a sound and complementary combination of auxiliary organ support techniques.